If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying a + -1(9b + -13b) = 0 Combine like terms: 9b + -13b = -4b a + -1(-4b) = 0 Remove parenthesis around (-4b) a + -1 * -4b = 0 Multiply -1 * -4 a + 4b = 0 Solving a + 4b = 0 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-4b' to each side of the equation. a + 4b + -4b = 0 + -4b Combine like terms: 4b + -4b = 0 a + 0 = 0 + -4b a = 0 + -4b Remove the zero: a = -4b Simplifying a = -4b
| 3+5n=35 | | -7x-10=59 | | 25t=30(t+10) | | 2j+18=32 | | 8z+4(5z+10)=0 | | 3y+9=2y-5 | | s/12=21/2 | | -7+40y=35y-6 | | n^2+1n-13=0 | | 17+13x=165 | | 2ln(x+2.8)=3.2 | | -4/5 | | 5-3x+7x=-39 | | 2(9s+4)-8=2(5s+3)-8 | | 4n-10n+35=1.2 | | 3x+x^2=48 | | 8/9g=1/3 | | 2x-8/=7 | | 2y^2+13y-45=0 | | -4r=21+3r | | 46+3x=5x-7 | | 550=7x+3y | | 2/7x-4=6 | | -y*4=12 | | 3x+4/5=5 | | d=1/2mv | | x*0.8+x*0.8+x=7.8 | | (4x+2)*(5)=112 | | (7-3)8= | | .05x+20=.07x+10 | | x*0.8+x*0.8=7.8 | | -2x-4=3x-4 |